Synchronous Upper Squamous and Lower Adenocarcinoma of the Oesophagus: A Rarely Reported Case Treated with Palliative Chemotherapy and Stenting - Niall Hardy; Justin Kelly; John Conneely; Barry Kelleher (Case Reports in Gastrointestinal Medicine)
Oesophageal cancer is divided into two main subtypes, squamous and adenocarcinoma. It is the eighth most common cancer in the world with squamous more common in the developing world and adenocarcinoma most prevalent in the developed world. Incidences of concomitant squamous carcinoma with adenocarcinoma are exceedingly rare with only a few documented occurrences in the form of case reports existing. Here we report a case of synchronous squamous and adenocarcinoma of the oesophagus occurring in an 81-year-old lady with dysphagia, weight loss, and no identifiable risk factors.